The Prognostic Value of the Fracture Level in the Treatment of Displaced Supracondylar Humeral Fractures in Children - Gaihre, S. K.; Uprety, S.; Thapa, S. S. (Kathmandu University Medical Journal, 2020)
Background Supracondylar fractures are subclassified as high and low type depending on whether they are above or below the isthmus of the distal humerus and it play an important role in determining outcome. Objective To compare the clinical and radiological outcomes of patients with fractures above and below the distal humeral isthmus treated with closed reduction and percutaneous pinning. Method This is a prospective non-randomized analytical study of 40 patients with displaced extension type supracondylar fracture of distal humerus treated by closed reduction and percutaneous pinning. Radiological and functional outcomes was followed up to 6 months postoperatively. The significance of differences between means (baumann angle, carrying angle and time to recovery) were calculated using the independent t-test. Result Twenty-four (60%) patients were high type and 16 (40%) patients were low type. According to Flynn grading, there was no statistical significance between the high type and low type (p = 0.601). The time to recovery for the high type was 15.58 ± 2.95 weeks and for low type was 18.75 ± 2.18 weeks. Hence, the time to recovery for the low type was longer than high type and it was statistically significant (p = 0.001). Conclusion Low type supracondylar fractures require a longer period for the gain of elbow range of motion. However, in long term the prognosis of low type is comparable with that of high type fracture. Hence, the prognostic value of fracture level in the treatment of displaced supracondylar fractures is not statistically significant.